The I’rab Method of Habib Hasan Baharun: Impact on Arabic Grammar Instruction - Segaf Baharun; Muhamad Solehudin; Masnun; Syarif Muhammad Syaheed (Al-Muhawaroh: Jurnal Pendidikan Bahasa Arab, 2025)
Mastering Arabic syntax (nahwu), particularly the system of i‘rab (case inflection), poses persistent challenges for non-native learners in Islamic boarding schools (pesantren). This study investigates the pedagogical design and instructional impact of Kitab I’rab authored by Habib Hasan Baharun, founder of Pondok Pesantren Darullughah Wadda’wah (Dalwa), Indonesia. Employing a mixed-methods approach, the research involved 120 intermediate-level students and Arabic teachers through observations, interviews, and questionnaires. The findings reveal that the I’rab Method promotes grammatical awareness, student engagement, and instructional clarity through simplified explanations, contextual examples, and emotionally resonant content. This method contrasts sharply with traditional models by aligning with constructivist theory and integrating multimodal, affective, and cultural learning dimensions. The study concludes that the Kitab I’rab serves as an effective localized grammar tool that bridges classical Arabic rigor with contemporary learner needs. Its practical application offers a replicable model for other pesantren and Islamic institutions seeking to revitalize Arabic grammar education.